Pengaruh Penggunaan Instagram Terhadap Perilaku Fear of Misisng Out (Studi pada Mahasiswa Ilmu Komunikasi Angkatan 2018-2020 Universitas Pattimura) - Lahia, Tabita Laurenchia; Salakay, Selvianus; Bandjar, Antasari (Jurnal Ilmu Komunikasi Pattimura, 2022)
This study aims to determine the Influence of Instagram Use on Fear of Missing Out Behavior (Study on Communication Science Students Class of 2018-2020 Pattimura University Ambon).This research is a quantitative research carried out at the Faculty of Social and Political Sciences, Pattimura University, Ambon. Primary data collection was carried out through the distribution of questionnaires to 100 Students of Communication Sciences, Pattimura University, Ambon, consisting of Students Class of 2018-2020. In this study, the sampling technique used was the Purposive Sampling technique and used data analysis techniques, namely simple regression analysis using SPSS (Statistical Product Service Solution) version 25 for windows.The results showed that the F value was 49.407, the R value was 0.579, the R square value was 0.335 with a significance value of 0.000 (p>0.01). This means that there is an influence of Instagram on fear of missing out behavior, which is 33.5% while 66.5% is influenced by other things outside the study. The empirical mean calculation value in the Instagram usage variable obtained a value of 39.8 is in the medium category and the fear of missing out behavior variable in the 30.2 value is in the medium category. Based on the results of the study, it shows that the hypothesis (H1) in this research is accepted. This means that there is an influence of the use of Instagram on the behavior of fear of missing out in Communication Science students class of 2018-2020 Pattimura University Ambon.